Failure Study of Concrete Pile Structures on Riverbanks in Singkawang - Raihan, Nabila Nur; Priadi, Eka; Rustamaji, Rustamaji (Jurnal Teknik Sipil, 2025)
Urban infrastructure development often faces geotechnical challenges, especially around rivers, where concrete piles are used to reinforce riverbanks. The stability of concrete piles is highly dependent on proper planning, construction, and maintenance, which is influenced by the quality of materials, construction methods, and environmental conditions. This study aims to determine the value of embedment depth (D) in concrete piles under normal conditions and when bearing embankment loads. The research was conducted on sheet piles on both sides of the river between Jalan Alianyang and Jalan Tani, Singkawang. Primary data used were the field and laboratory test results, including testing the physical and mechanical properties of the soil, while secondary data were obtained from the Regional Development Planning Agency (BAPEDDA). The results showed that the 8.577 m long sheet pile had an embedment depth (D) value of 4.917 m under normal conditions. However, the sheet pile collapsed when it withstood the embankment load of 65.374 kN/m ² due to dredging using an excavator. Based on the analysis, the sheet pile that can withstand the load requires a length of 12.555 m with an embedment depth (D) of 8.895 m.